The Color Purple and Women's Time - Sedehi, Kamelia Talebian; Talif, Rosli; Wan Yahya, Wan Roselezam; Jujar Singh, Hardev Kaur (Academy Publisher, 2014)
In Women's Time, Julia Kristeva asserts that women have been deprived of linear time for progress and improvement; they have been confined to circular time, which is a vicious circle of repetition; therefore she asked for the existence of a third generation of feminists to focus on linear time and to provide the ground for women's social as well as domestic roles. She mentions that the third feminists' duty is to pay attention to the individuality of each woman. In The Color Purple, Alice Walker's female protagonist, Celie, revolts against fixed gender roles. She unites with other female characters and has a sisterhood relationship. This article intends to focus on the effect of patriarchal system on women. Moreover, it will highlight sisterhood and its effect on women's individuality and social roles. As such, this article intends to focus on Julia Kristeva's notion of women's time and the way Celie intends to follow her desires. The attention to Celie's passions and desires in life helps her to know herself better.